Pelatihan pembuatan pupuk organik cair (POC) berbahan bonggol pisang di komunitas Unsulbar Farming Club (UFC) - Nadia, Nadia; Muthmainnah, Muthmainnah; Herlianti, Anita; Nurhikma, Nurhikma; Alfarizi, Ismul Faqih (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2024)
The objectives of community service conveyed through this outreach and training include: (1) Increasing the utilization of agricultural waste in the form of banana tubers into liquid organic fertilizer (POC); (2) Practicing how to make POC and applying it to land. This service activity uses the Contextual Teaching and Learning (CTL) method. In implementing this service, an approach is taken with the community, especially students, as the target of the activity. This service activity was carried out at the Green House of the University of West Sulawesi, with the participants being all students of the Agroecotechnology Study Program at the University of West Sulawesi class of 2022. In this service activity, an explanation of POC production made from banana tubers and how to make it was carried out by students who take part in the training, with the material presented being obtained during the lecture period so that students have mastered the material regarding the benefits and how to make POC. The participants’ responses showed they were enthusiastic about participating in this activity. This was proven by statements from participants stating that they understood the material presented by West Sulawesi University students in this service.